2011
DOI: 10.1038/cddis.2011.41
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of lipid rafts in the localization and dysfunction effect of the antitumor ether phospholipid edelfosine in mitochondria

Abstract: Lipid rafts and mitochondria are promising targets in cancer therapy. The synthetic antitumor alkyl-lysophospholipid analog edelfosine (1-O-octadecyl-2-O-methyl-rac-glycero-3-phosphocholine) has been reported to target lipid rafts. Here, we have found that edelfosine induced loss of mitochondrial membrane potential and apoptosis in human cervical carcinoma HeLa cells, both responses being abrogated by Bcl-xL overexpression. We synthesized a number of new fluorescent edelfosine analogs, which preserved the proa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
0
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(110 citation statements)
references
References 39 publications
8
88
0
14
Order By: Relevance
“…First, we found that all pancreatic cancer cell lines used in this study incorporated high amounts of drug ( Figure 1c). Next, we found that the new fluorescent edelfosine analog 1-O-[11 0 -(6 00 -ethyl-1 00 ,3 00 ,5 00 ,7 00 -tetramethyl-4 00 ,4 00 -difluoro-4 00 -bora-3a 00 ,4a 00 -diaza-s-indacen-2 00 -yl)undecyl]-2-O-methylrac-glycero-3-phosphocholine (Mollinedo et al, 2011) accumulated in the ER of HuP-T4 and Capan-2 cells (Figure 2a), as assessed using a version of red fluorescence protein targeted to the ER lumen (ER-targeted red fluorescence protein), which completely co-localized with the ER marker calreticulin (Klee and PimentelMuinos, 2005). Incorporation of fluorescent 1-O-[11 0 -(6 00 -ethyl-1 00 ,3 00 ,5 00 ,7 00 -tetramethyl-4 00 ,4 00 -difluoro-4 00 -bora-3a 00 , 4a 00 -diaza-s-indacen-2 00 -yl)undecyl]-2-O-methyl-rac-glycero-3-phosphocholine into the cells was blocked by adding the parent drug edelfosine (data not shown), thus behaving as a reliable edelfosine fluorescent analog to visualize the subcellular location of the drug 'in situ'.…”
Section: Induction Of Apoptosis By Edelfosine and Other Alps In Humanmentioning
confidence: 97%
See 1 more Smart Citation
“…First, we found that all pancreatic cancer cell lines used in this study incorporated high amounts of drug ( Figure 1c). Next, we found that the new fluorescent edelfosine analog 1-O-[11 0 -(6 00 -ethyl-1 00 ,3 00 ,5 00 ,7 00 -tetramethyl-4 00 ,4 00 -difluoro-4 00 -bora-3a 00 ,4a 00 -diaza-s-indacen-2 00 -yl)undecyl]-2-O-methylrac-glycero-3-phosphocholine (Mollinedo et al, 2011) accumulated in the ER of HuP-T4 and Capan-2 cells (Figure 2a), as assessed using a version of red fluorescence protein targeted to the ER lumen (ER-targeted red fluorescence protein), which completely co-localized with the ER marker calreticulin (Klee and PimentelMuinos, 2005). Incorporation of fluorescent 1-O-[11 0 -(6 00 -ethyl-1 00 ,3 00 ,5 00 ,7 00 -tetramethyl-4 00 ,4 00 -difluoro-4 00 -bora-3a 00 , 4a 00 -diaza-s-indacen-2 00 -yl)undecyl]-2-O-methyl-rac-glycero-3-phosphocholine into the cells was blocked by adding the parent drug edelfosine (data not shown), thus behaving as a reliable edelfosine fluorescent analog to visualize the subcellular location of the drug 'in situ'.…”
Section: Induction Of Apoptosis By Edelfosine and Other Alps In Humanmentioning
confidence: 97%
“…The subcellular localization of edelfosine in pancreatic cancer cells was examined with the newly synthesized edelfosine fluorescent analog 1-O-[11 0 -(6 00 -ethyl-1 00 ,3 00 ,5 00 ,7 00 -tetramethyl-4 00 ,4 00 -difluoro-4 00 -bora-3a 00 ,4a 00 -diaza-s-indacen-2 00 -yl)undecyl]-2-O-methyl-rac-glycero-3-phosphocholine (Mollinedo et al, 2011), a kind gift from F. Amat-Guerri and A. U. Acun˜a (Consejo Superior de Investigaciones Cientı´ficas, Madrid, Spain). ER was visualized by transfecting cells with 4 mg of a plasmid encoding ER-targeted red fluorescence protein (Klee and Pimentel-Muinos, 2005), kindly provided by FX Pimentel-Muinos (Instituto de Biologı´a Molecular y Celular del Ca´ncer, Centro de Investigacio´n del Ca´ncer, Salamanca, Spain).…”
Section: Drug Subcellular Localizationmentioning
confidence: 99%
“…The plasma membrane (PM) 4 of eukaryotes represents one of the most complex biomembranes, featuring an asymmetric lipid distribution between the two leaflets of the bilayer as well as lateral domain organization within leaflets. Lipid rafts are dynamic areas of the membrane rich in sterols and sphingolipids that serve as platforms for the association of membrane proteins.…”
mentioning
confidence: 99%
“…Mechanisms involved in edelfosine-induced apoptosis include formation of plasma membrane lipid rafts recruiting death receptor and downstream apoptotic signaling molecules [14,16,19,20,24,25,27], endoplasmic reticulum (ER) stress response [13,17,20,29,30], mitochondrial depolarisation [20,25,35], cytochrome c release [13], caspase activation [3,13,16,23] and generation of reactive oxygen species [13,31,35].…”
Section: Introductionmentioning
confidence: 99%